2016
DOI: 10.1093/mnras/stw2219
|View full text |Cite
|
Sign up to set email alerts
|

A high-resolution H i study towards the supernova remnant Puppis A and its environments

Abstract: We observed the supernova remnant (SNR) Puppis A in the 21 cm line with the Australia Telescope Compact Array with the aim of determining the systemic velocity and, hence, the corresponding kinematic distance. For the compact, background sources in the field, we obtain absorption spectra by applying two methods: (a) subtracting profiles on-and off-source towards continuum emission, and (b) filtering short spacial frequencies in the Fourier plane to remove large scale emission. One of the brightest features to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 34 publications
2
52
0
1
Order By: Relevance
“…Note-a Since no direct measurement exists, we inferred the values from an evolutionary model by Chevalier & Oishi (2003) with an assumption of the ejecta mass of 5 M ⊙ , a mass-loss rate of 2×10 −5 M yr −1 , and a stellar wind speed of 10 km s −1 . References are as follows: [1] Reed et al (1995) [2] Fesen et al (2006) [3] Gotthelf et al (2001) [4] Tananbaum (1999) [5] Gaensler & Wallace (2003) [6] Winkler et al (2009) [7] Bhalerao et al (2015) [8] Hughes et al (2003) [9] Reynoso et al (1995) [10] Reynoso et al (2017) [11] Becker et al (2012) [12] Gotthelf & Halpern (2009) [13] Gotthelf et al (2013) [14] Winkler et al (1988) [15] Tian & Leahy (2008) [16] Wachter et al (2004) [17] Vasisht & Gotthelf (1997) [18] Paron et al (2006) [19] Carter et al (1997) [20] Garmire et al (2000) [21] De Luca et al (2006) [22] Esposito et al (2011) [23] Feast (1999) [24] Park et al (2012) [25] Kulkarni et al (2003). Note-The region names in the first row correspond to those in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Note-a Since no direct measurement exists, we inferred the values from an evolutionary model by Chevalier & Oishi (2003) with an assumption of the ejecta mass of 5 M ⊙ , a mass-loss rate of 2×10 −5 M yr −1 , and a stellar wind speed of 10 km s −1 . References are as follows: [1] Reed et al (1995) [2] Fesen et al (2006) [3] Gotthelf et al (2001) [4] Tananbaum (1999) [5] Gaensler & Wallace (2003) [6] Winkler et al (2009) [7] Bhalerao et al (2015) [8] Hughes et al (2003) [9] Reynoso et al (1995) [10] Reynoso et al (2017) [11] Becker et al (2012) [12] Gotthelf & Halpern (2009) [13] Gotthelf et al (2013) [14] Winkler et al (1988) [15] Tian & Leahy (2008) [16] Wachter et al (2004) [17] Vasisht & Gotthelf (1997) [18] Paron et al (2006) [19] Carter et al (1997) [20] Garmire et al (2000) [21] De Luca et al (2006) [22] Esposito et al (2011) [23] Feast (1999) [24] Park et al (2012) [25] Kulkarni et al (2003). Note-The region names in the first row correspond to those in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The ATCA configurations were EW 352 and 750A for the first and second 13hr runs respectively, so that the visibilities correspond to baselines between 31 and 735 m excluding the 6th, fixed antenna. A thorough analysis of the continuum data was published in Reynoso & Walsh (2015), while the Hi 21 cm line study was reported in Reynoso et al (2017). The primary flux and bandpass calibrator was PKS 1934-638, while PKS 0823-500 was used for phase and polarization calibration.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…The data reduction was carried out with the miriad software package (Sault et al 1995). The observations in the EW 352 array were affected by a bug which was fixed as described in Reynoso et al (2017). The uv data were split in eleven bands of 128 MHz, centered at frequencies from 1302 to 2582 MHz.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…The image displays the radio continuum emission produced at 1.4 GHz. It was published by Reynoso & Walsh (2015), and reproduced by Reynoso et al (2017). Right: A full view of Puppis A in X-ray, where red, green, and blue correspond to the 0.3-0.7, 0.7-1.0, and 1.0-8.0 keV bands, respectively (from Dubner et al 2013).…”
Section: Supernova Remnants With Earsmentioning
confidence: 99%